STEM Activities Integrated with Drama: STEM+drama - Öcal, Erdinç (My University, 2022)
This study aimed to determine secondary school students’ views of STEM activities integrated with drama (STEM+drama) in seventh-grade math teaching. The study adopted phenomenology, which is a qualitative research design. The sample consisted of 22 seventh-grade students. Data were collected using a semi-structured interview form. A focus group discussion was held with eight participants. Observations were made throughout the process. The data were analyzed using inductive content analysis. STEM+drama activities turned abstract math concepts into interesting and fun representations and helped participants enjoy learning them. STEM+drama activities made participants feel actively engaged in their own learning. Participants suggested that similar activities be integrated into other courses. STEM+drama activities stimulated participants and made them more enthusiastic about searching, questioning, and learning. STEM+drama activities also helped them develop social and academic skills and improve their interests and motivation. The results were discussed in light of the literature, and recommendations were made for further research.